Trilingual talk in Sicilian-Australian migrant families playing out identities through language alternation - Rubino, Antonia; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book explores the linguistic and cultural identities of Sicilians in Australia, through conversations gathered within the family, survey data and interviews. The study is placed in the context of the family migrant experience and the shifting attitudes towards immigrant languages in Australia.
Keywords: Linguistics; Applied linguistics; Comparative linguistics; Historical linguistics; Sociolinguistics; Emigration and immigration